Energy policy in transitional economies: The case of Bulgaria - Federico Foders (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
For several decades, the countries in Central and Eastern Europe pursued an energyintensive strategy of economic development based on distorted relative prices of energy. This typical feature of central planning created the illusion of a virtually unlimited supply of energy. The illusion came to an end in the 1980s, when the widening gap between energy supply and energy demand faced by the region led to a severe energy crisis. 9 Bulgaria is one of the countries most affected by the energy crisis in Central and Eastern Europe. Poorly endowed with energy resources, Bulgaria relies largely on international trade to satisfy its demand for energy. During Bulgaria's membership in the CMEA, energy-intensive growth resulted in a strong dependency on only one energy exporter, the former Soviet Union. With the CMEA's dissolution, Bulgaria was left to design and implement a new energy policy as a part of its own efforts to transform its economy into a market economy. In spite of the far-reaching liberalization of prices experienced by Bulgaria in 1991, economic transition has been rather slow and energy reform has been neglected. Domestic energy prices have remained under government control, and energy prices have been falling in real terms due to the high overall inflation. Domestically produced primary energy is not priced at international levels, and consumer prices for final energy do not reflect domestic production costs. Moreover, current energy pricing favours small-scale users (households) and discriminates against large-scale users (industry). The continuing high level of energy consumption and the prevailing fuel mix (oil products and lignite) have a particularly adverse effect on the environment in terms of SO2 and CO2 emissions. In the short run, energy policy should concentrate on the liberalization of domestic energy prices. Primary energy should be priced at world market prices and final energy at marginal costs. A realistic valuation of energy products will support the structural change component of the transformation process and increase energy efficiency in Bulgaria. A policy of fuel diversification complemented by one of regional diversification of energy imports will constitute the best long-run hedge against the risk of supply disruptions. Energy utilities should be privatized, and foreign companies should be allowed to play a leading role in the modernization of the energy sector. The Bulgarian government should create optimal conditions for cooperating closely with EC member countries in the field of energy, as already delineated in the European Energy Charter and in Bulgaria's Association Treaty with the EC. As long as sophisticated emission fees can be neither implemented nor enforced, energy-related environmental pollution should be dealt with by taxing energy use at the consumer level with a simple uniform ad valorem rate applied to all fuels.
Keywords: 330; Energiepolitik; Systemtransformation; Energiewirtschaft; Bulgarien